Utilization of agro-industrial vegetable residues in bakery products: Systematic review on nutritional, technological and sensory impact (Research, Society and Development, 2026)
The vegetable processing industry generates a massive volume of by-products, such as peels and pomace, which are frequently discarded despite their high nutritional potential. This systematic review aimed to evaluate the technical feasibility and consolidate evidence regarding the nutritional, technological, and sensory impact of incorporating vegetable by-product flours into bakery products. The bibliographic survey covered the ScienceDirect, MDPI, and SciELO databases, spanning the period from 2009 to 2025. The results demonstrated that the utilization of these residues significantly increases the content of fibers, minerals, and bioactive compounds in the products. However, it was observed that the addition of insoluble fibers interferes with the gluten network and water absorption, resulting in technological challenges such as reduced specific volume and increased crumb hardness. Sensory analysis indicated that acceptance is not linear, with the ideal substitution limit lying between 5 and 10% for yeast-leavened breads and up to 20% for cookies and gluten-free products. It is concluded that the utilization of waste in bakery is a viable circular economy strategy, transforming low-cost ingredients into functional foods, provided that formulation limits are respected to ensure technological quality.